Outcomes of Covid-19 on Nasal Disorders and Assessment of Quality of Life in Post-Covid Patients. (Texas Journal of Medical Science, 2022)
Studies and discussions about different forms of presentation began to spread COVID-19 and its consequences and effects, including olfactory imbalances such as sleep disturbances, anxiety and depression, activity, and breathing.